Pengaruh Perawatan Man Hole dan Pemahaman Prosedur Enclosed Space Terhadap Keselamatan Kerja Crew di Kapal MV. Tanto Jaya - Alviyan Adi Saputro; Retno Indriyati; Gita Kusumawardani (JURNAL BARTEK, 2025)
This study aims to analyze the influence of manhole maintenance and the understanding of enclosed space procedures on the safety of the crew aboard the MV. Tanto Jaya. Manholes and enclosed spaces are areas with high potential risks in ship operations, particularly concerning exposure to hazardous gases and oxygen deficiency. Therefore, proper manhole maintenance and a good understanding of safety procedures are crucial factors in preventing accidents. The research method used is a qualitative approach, involving interviews with the ship's crew. The results of the study show that optimal manhole maintenance and sufficient understanding of enclosed space procedures significantly influence the improvement of work safety on the ship. Crews with a good understanding of safety procedures and regular training on manhole maintenance show lower accident rates. This research is expected to contribute to efforts to improve work safety standards on ships, especially in risk management related to enclosed spaces and manhole maintenance.